The Relationship Between Maternal Eating Behavior and Infant Eating Behavior: A Cross-Sectional Study - Rahmi Nurrasyidah; Lutfiana Puspita Sari (Nurul Ilmi : Journal of Health Sciences and Midwifery, 2026)
Introduction: A mother's eating habits are influenced by various factors. These habits influence her child's attitudes and behaviors regarding feeding. A mother's eating patterns become the prototype for a toddler's eating patterns. Objective: The aim of this research is to determine the effect of maternal eating behavior and feeding mode on toddler eating behavior. toddler eating behavior observed among picky eaters and eating disorders. Method: This study used a cross-sectional design. The study was conducted from January to September 2025. Primary data was used for data collection. Data processing and analysis were conducted using univariate and bivariate analysis. The population was all toddlers in Ngrundul Kebonarum village. Consecutive sampling was used to select 60 mothers of toddlers. The instrument used is the Healthy Eating Assessment for maternal eating behavior and the Infant and Child Feeding Questionnaire (ICFQ) for toddler eating behavior Result: Based on our study, there is no significant relationship between maternal eating behaviour and picky eating behavior in toddlers where p Value >0.05. Second result, there is no significant relationship between maternal eating behaviour and eating behavior in toddlers related to eating disorders where p Value = 0.05. Conclusion: There is no significant relationship between maternal eating behavior and toddler eating behavior. Future research should include a larger sample size and measures of several other factors that influence toddler eating patterns and  improving case-control research methods is also needed to specifically measure the influence of maternal eating behavior on toddler eating behavior. Implications for clinical practice include identifying maternal eating behaviors to further educate toddlers about balanced diets.